Rank‐Order Tournaments and Incentive Alignment: The Effect on Firm Performance - KALE, JAYANT R.; REIS, EBRU; VENKATESWARAN, ANAND (Journal of Finance, 2009)
ABSTRACT We investigate simultaneously the impact of promotion‐based tournament incentives for VPs and equity‐based (alignment) incentives for VPs and the chief executive officer (CEO) on firm performance. We find that tournament incentives, as measured by the pay differential between the CEO and VPs, relate positively to firm performance. The relation is more positive when the CEO nears retirement and less positive when the firm has a new CEO, and weakens further when the new CEO is an outsider. Our analysis is robust to corrections for endogeneity of all our incentive measures and to several alternative measures of tournament incentives and firm performance.